Life expectancy and health-adjusted life expectancy are decreased in people living with inflammatory bowel disease: a population-based matched cohort study. (2018) - Kuenzig, Ellen; Manuel, Doug; Donelle, Jessy; Benchimol, Eric
No abstract available